Review of cloud based trust model - GU Xin; XU Zheng-quan; LIU Jin (Tongxin xuebao)
Combining the concepts of trust and cloud,the trust evaluation model of security application was discussed from the perspective of subjective.The fuzziness and randomness subjective description to network objects and the reli-ability of the information evaluation could be provided by cloud based trust model（CTM）,and it also,improving the se-curity of network applications,determined the trust level of entire information system.By reviewing the implement prin-ciple,classic improvement and existing problems,the mechanism of CTM could be analyzed,and the development direc-tions for CTM were pointed out.